2019
DOI: 10.1155/2019/9218251
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Variables Affect Meiotic Cell Cycle Progression, Tumor Ploidy, and Cancer-Associated Mortality in a brca2-Mutant Zebrafish Model

Abstract: Successful cell replication requires both cell cycle completion and accurate chromosomal segregation. The tumor suppressor BRCA2 is positioned to influence both of these outcomes, and thereby influence genomic integrity, during meiotic and mitotic cell cycles. Accordingly, mutations in BRCA2 induce chromosomal abnormalities and disrupt cell cycle progression in both germ cells and somatic cells. Despite these findings, aneuploidy is not more prevalent in BRCA2-associated versus non-BRCA2-associated human cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 74 publications
(123 reference statements)
1
19
1
Order By: Relevance
“…Surprisingly, brca2 mutation in females significantly reduced the survival rate after they have developed tumors compared to males with the same genotype. This study further supports the link between brca2 mutation and cancer aneuploidy with poor survival prognosis [47].…”
Section: Genetic Models Of Cancer In Zebrafishsupporting
confidence: 86%
See 1 more Smart Citation
“…Surprisingly, brca2 mutation in females significantly reduced the survival rate after they have developed tumors compared to males with the same genotype. This study further supports the link between brca2 mutation and cancer aneuploidy with poor survival prognosis [47].…”
Section: Genetic Models Of Cancer In Zebrafishsupporting
confidence: 86%
“…Recently, brca2 mutant zebrafish in a tp53 -/- background were examined for cell cycle arrest and genomic stability. This model, as it is not embryonically lethal compared to many BRCA2 mouse models, allows for in vivo studies in adult animals [47]. In brca2 mutant zebrafish, it was previously shown that there is an increased incidence of benign testicular tumors [48].…”
Section: Genetic Models Of Cancer In Zebrafishmentioning
confidence: 99%
“…To determine how injury and regenerative responses affect ocular tumorigenesis in zebrafish, we analyzed tumor development in brca2 m/m;tp53 m/m and tp53 m/m zebrafish that received unilateral ONI at three months of age. The ONI group was compared to brca2 m/m;tp53 m/m and tp53 m/m zebrafish from a previously reported cohort, designated as the control group 27 (see Methods and Table S4 for details). Tumor development in ONI and control groups is summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, brca2 homozygous zebrafish derived from heterozygous parents are fully viable and survive to adulthood. Since cancer susceptibility in zebrafish with brca2 mutation alone is low 25 , we use zebrafish with combined mutations in brca2 and tp53 26 for carcinogenesis studies 25,[27][28][29] . The brca2-mutant zebrafish model provides a unique in vivo system for determining how loss of functional BRCA2 affects various developmental, adult, and cancer-associated phenotypes 25,[27][28][29] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation